THE ROLE OF KREDIT USAHA RAKYAT (KUR) TO MICRO AND SMALL BUSINESS DEVELOPMENT IN CITY BANDAR LAMPUNG - Anggraini, Evi Novaria; bin Mohd Sam, Mohd Fazli (Prosiding International conference on Information Technology and Business (ICITB), 2016)
This research is to investigate the effects of private capital and the role of the Micro Credit Program capital (KUR) for the development of small and micro-businesses (SMEs) in Bandar Lampung City. The research was conducted through questionnaires survey. The respondents were micro entrepreneurs who have received loan and Kredit Usaha Rakyat (KUR) The types of data which gained was a primary data. It was obtained through a questionnaire survey techniques. At the same time, data analysis technique also have been used is multiple regression analysis. The results of this study show that there are positive and significant impact on a micro business operators in Bandar Lampung City which used individual capital or capital of Kredit Usaha Rakyat.(KUR). It can be conclude, the higher capital invested in the company, the income gained by the micro entrepreneur will be increase in Bandar Lampung city. KEY WORDSMicro and Small Enterprises (MSEs), Business Development, and Kredit Usaha Rakyat (KUR).